Beauty influencer in the digital age: How does it influence purchase intention of generation Z? - Hanif Adinugroho Widyanto; Cahya Rahmania Agusti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This research examined the influence of social media advertising conducted by beauty influencers. The researchers analyzed the impact of Celebrity Credibility (i.e., Expertise, Trustworthiness, and Attractiveness), Reputation, and Persuasive Capabilities toward Purchase Intention. The respondents in this research were 154 young women from Generation Z who lived in the Greater Jakarta (Jabodetabek) area and followed the social media beauty influencers who endorsed a renowned homegrown cosmetics brand. This research utilized a quantitative method using the Multiple Linear Regression analysis. The results of this study showed that only two independent variables associated with the beauty influencer, namely, Attractiveness and Persuasive Capabilities, yielded a significantly positive influence toward Purchase Intention. In contrast, the rest of the variables were not significant. All independent variables had a simultaneously significant impact on Purchase Intention. Finally, all independent variables contributed 72.4% to the dependent variable, while the rest were explained by other variables not examined in this research.